RNA-seq revealed the effects of heat stress on different brain regions of Leiocassis longirostris - Liu, Senyue; Li, Qiang; Deng, Yongqiang; Wang, Zhongwei; Feng, Yang; Zhao, Han; Zhao, Zhongmeng; Zhang, Lu; Duan, Yuanliang; Huang, Zhipeng; Zhou, Jian; Mou, Chengyan (Frontiers in Physiology, 2025)
Understanding how distinct brain regions of Leiocassis longirostris molecularly adapt to heat stress is vital for improving aquaculture sustainability and guiding conservation strategies in a warming climate. To elucidate the region-specific molecular mechanisms underlying heat stress responses in the brain of L. longirostris, we exposed L. longirostris to acute heat stress (32°C) for 24 h and performed RNA-seq and WGCNA on five brain regions (OB: olfactory bulb, FB: pituitary, hypothalamus, forebrain, MB: mesencephalon, CB: cerebellum, and SC: spinal cord). The results showed that, after heat stress, the FB region significantly activated the ER stress pathway, and the abnormal proteins were synergically cleared by HSP-mediated UPR (such as Hsp70, Hsp90, IRE1α, Perk, ATF6) and UPS-mediated ERAD (such as UBE2, UBE3, TRIM63). Meanwhile, the SC region showed marked downregulation of lipid metabolism and PPAR signaling pathway, suggesting energy conservation as a compensatory strategy. WGCNA further highlighted the FB as the hub for ER stress and the SC for metabolic suppression. In conclusion, our study suggests that distinct brain regions of L. longirostris adopt different strategies under heat stress, in which the FB region mediates protein quality control and the SC region drives metabolic inhibition. These findings highlight the adaptation strategies of the L. longirostris brain to heat stress and provides a potential target for improving its survival under global warming.